Long-term fertilization effect of organic carbon and total nitrogen on floodplain soil - Majharul Islam, Md.; Forhad Hossain, Md.; Mukul Mia, Md; Shaidul Islam, Md.; Saikat Hossain Bhuiyan, Md.; Alam Talukder, Joynul; Abdul Kader, M. (International Journal of Advanced Geosciences, 2019)
Soil organic matter is the most often reported indicator of soil quality and productivity and an evidence of previous soil management. Therefore, in 2017, a laboratory incubation study was carried out in the experimental filed of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, Bangladesh under control condition at 25°C for 104 days to investigate the influence of long term manuring and fertilization on soil respiration by means of C mineralization. Soil samples were collected from floodplain soil with rice-rice cropping pattern at Bangladesh Agricultural University (BAU) experimental farm having eight treatments. Long term (33 years) application of fertilizers and manure resulted in significant differences in soil organic carbon, total N content, and soil pH KCl between the treatments. The soil organic carbon and total N content varied among the different treatments from14.9 g OC kg-1 to 17.0 g OC kg-1 and1.60 g N kg-1 (control) to 1.78 g N kg-1 (application of NPK). The soil pH varied among the different treatments from 5.65(application of NK) to 4.89 (application of N). This result indicates that more stable organic carbon was formed in NPK treated soil which is less prone to decomposition if present crop management has been changed.